2018
DOI: 10.1590/1414-431x20187252
|View full text |Cite
|
Sign up to set email alerts
|

Association between serotonin 2C receptor gene (HTR2C) polymorphisms and psychopathological symptoms in children and adolescents

Abstract: Serotonin 2C receptors (5HT2C) are involved in serotonin-driven dynamic equilibrium adjustments responsible for homeostatic stability in brain structures that modulate behavior and emotions. Single nucleotide polymorphisms (SNPs) from the serotonin 2C receptor gene (HTR2C) have been associated with several neurological and mental disorders, including abnormalities in cognitive and emotional processes. The aim of this study was to evaluate the association between the rs6318 SNP of the HTR2C gene and behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As illustrated in Table 1 , there were no significant differences in demographic or substance use parameters, difference in abstinence time between the first and second scans (three participants had missing data), route of cocaine administration, nor the number of days between the placebo and mirtazapine scans for the wild-type and HTR2C SNP subgroups. The frequency (~50%) of the HTR2C SNP in our largely African American pool was higher than expected in the general population (~20%) (1000 Genome [ 53 ]). Among all the 28 participants, 22 smoked cocaine and six used cocaine intranasally (Table 1 ).…”
Section: Resultsmentioning
confidence: 54%
“…As illustrated in Table 1 , there were no significant differences in demographic or substance use parameters, difference in abstinence time between the first and second scans (three participants had missing data), route of cocaine administration, nor the number of days between the placebo and mirtazapine scans for the wild-type and HTR2C SNP subgroups. The frequency (~50%) of the HTR2C SNP in our largely African American pool was higher than expected in the general population (~20%) (1000 Genome [ 53 ]). Among all the 28 participants, 22 smoked cocaine and six used cocaine intranasally (Table 1 ).…”
Section: Resultsmentioning
confidence: 54%
“…On the other hand, in adolescent controls T/C haplotype of rs4142900-rs9534512 was associated with the increased aggressive behaviors [ 92 ]. Other serotonin receptor encoding gene polymorphisms, including 5-hydroxytryptamine receptor 1B [ 93 , 94 ] , 1E [ 95 ] and 2 C [ 96 ] further demonstrated significant effects on childhood aggression ( Table 1 ) . Lastly, a recent comprehensive study analyzing the association between polygenic score indexing serotonin functioning and aggression demonstrated that adolescents with higher serotonin polygenic risk (lower levels of serotonin functioning) had an increased risk for aggressive and antisocial behaviors [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…G-allele carriers in group-based intervention showed little improvement during the intervention and a worsening of symptoms during the follow-up year, while those receiving the individual format demonstrated reductions in externalizing problems. Paes [ 96 ] Association between serotonin 2 C receptor gene (HTR2C) polymorphisms and psychopathological symptoms in children and adolescents. Outpatient psychiatric unit of the Universidade Estadual de Campinas (UNICAMP) Hospital Brazilian sample (otherwise unspecified) -- from Amilton dos Santos Júnior et al 2015 ( https://www.liebertpub.com/doi/10.1089/cap.2015.0094 ): >50% white, then others -- mixed, black, yellow skin colors M; F 8–18 85 (65 M) Candidate gene HTR2C rs6318 CBCL The presence of the G allele was found to be associated with aggressive behavior ( p = 0.033), and aggressive behavior was found to be associated with heterozygosis in females.…”
Section: Methodsmentioning
confidence: 99%
“…Some single nucleotide polymorphisms (SNPs) in Apolipoprotein E (APOE), Brain Derived Neurotrophic Factor (BDNF), Glutathione S-Transferase Pi 1 (GSTP1) and Paraoxonase 1 (PON1) genes, have shown a possible role in pathways related with metal neurotoxicity (Gaynor et al 2009;Benke et al 2014;Trucco et al 2018;Della Torre et al 2018;Paes et al 2018;Cimino et al 2020;Lozano et al 2021;Treble-Barna et al 2022). For instance, a Taiwanese study (Ng et al 2015) observed that children's carriers of APOE ε4 showed a higher risk of internalizing and externalizing problems with increasing mercury at the age of two years.…”
Section: Introductionmentioning
confidence: 99%